Ce qui aurait pu être et ne fut pas. Une perspective cinématographique de la psychiatrie catalane en exil - Cristina Bernaldo (Cahiers de Civilisation Espagnole Contemporaine)
Francesc Tosquelles, a psychiatrist in exile since the end of the Spanish Civil War, practiced in the Saint Alban mental health facility located in Lozère, after spending several month in the Septfonds refugee camp. He stayed in Saint Alban for most of the Second World War, overcoming the “soft extermination” period, on which French psychiatry has only conducted limited investigations, with no loss of lives. We will look into how his audiovisual testimony retains the pursuit of the psychiatry as it was before and during the Spanish second republic and how it will develop further in France.